PENGARUH HARGA, KUALITAS DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN JENANG TEGUH RAHARDJO DI KABUPATEN PONOROGO. (Studi Pada Industri Jenang Teguh Rahardjo) - kurniawan, deny (Universitas Slamet Riyadi, 2021)
This study aims to determine the effect of price, quality and packaging design on Teguh Raharjo jenang purchasing decisions in Ponorogo district. The population in this study were all buyers in Teguh Raharjo in Ponorogo district in February March 2020 as many as 150 respondents. In this study, the sample technique used was purposive sampling, namely sampling in accordance with what the researcher wanted, The number of samples in this study were 57 respondents. the analysis technique uses multiple linear regression with the classical assumption test. The analysis results obtained (X1) price, (X2) quality, (X3) packaging design with reliability test is reliable. Multicolinearity test passes the test, heterocedasdicity passes the test, autocorrelation passes the UI and the normality passes the test, The results showed that price, quality and packaging design had a positive effect on Teguh Raharjo's jenang purchasing decisions in Ponorog district. The research suggestion is that the company should always develop the quality of jenang products and make innovations about the packaging design of jenang products and pay attention to prices so that consumers always buy jenang products at Teguh Raharjo